2015
DOI: 10.5713/ajas.14.0504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corn and Soybean Meal Types on Rumen Fermentation, Nitrogen Metabolism and Productivity in Dairy Cows

Abstract: Twelve multiparous Holstein dairy cows in mid-lactation were selected for a replicated 4×4 Latin square design with a 2 ×2 factorial arrangement to investigate the effects of corn and soybean meal (SBM) types on rumen fermentation, N metabolism and lactation performance in dairy cows. Two types of corn (dry ground [DGC] and steam-flaked corn [SFC]) and two types of SBM (solvent-extracted and heat-treated SBM) with different ruminal degradation rates and extents were used to formulate four diets with the same b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
(69 reference statements)
3
12
2
1
Order By: Relevance
“…In the present study, a similar total VFA concentration in heifers fed SFC and FGC was observed. Consistent with our study, the total rumen VFA production was similar to animals fed FGC or SFC (Corona et al 2005;Shen et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, a similar total VFA concentration in heifers fed SFC and FGC was observed. Consistent with our study, the total rumen VFA production was similar to animals fed FGC or SFC (Corona et al 2005;Shen et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Synchronizing the rate of supply of ruminal energy and nitrogen sources was proposed as a potential method to improve MPS in ruminants [8,13]. According to previous studies [14,15,49], the release rate of energy other than protein mattered in synchrony. In situ rumen degradation showed that the water-soluble and rapidly degradable protein fraction of soybean meal is about 27%, and the in vitro crude protein degradation rate of soybean meal can be up to 60% in the first 6 h of incubation [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The diets adjusted had better energy and nitrogen level compared with the corresponding requirements of dairy cows. Dairy cow has low nitrogen use efficiency (about 25%) (Shen et al, 2015;Stádník and Atasever, 2017), and the improvement of efficiency is a special concern for animal farms, especially for dairy farms (Higgs et al, 2012;Maji et al, 2017). According to Pell (1992), the nitrogen excretion will decrease about 10% if the CP content in diets decreases by 1%.…”
Section: Results and Discussion Diagnosis And Adjustment Of The Ratiomentioning
confidence: 99%
“…The milk yields of medium-yield cows didn't show the same difference but showed that the diet had balanced MP and ME content before and after the diet adjustment. Moreover, the balance of diet MP and ME should be a benefit on improving utilization efficiency of diet nitrogen and decreasing environmental pollution (Shen et al, 2015).…”
Section: Effect Of Diet Adjustment By Cpm Model On Dmi Performance Amentioning
confidence: 99%